Quantenstochastik und Quantenfeldtheorie: 27.03. - 02.04.1994 - Accardi, Luigi; Waldenfels, Wilhelm von (Tagungsbericht, 1994)
Luigi Accardi; Robert Alicki; Claudio D'Antoni; Irina Arefeva; Vjacheslav P. Belavkin; Gari Efimov; Mark Fannes; George W. Ford; John Gough; Robin L. Hudson; Palle E.T. Jorgensen; Joachim Kupsch; Hajo Leschke; J. Martin Lindsay; Lu Yun Gang; Michael Schürmann; Michael Skeide; Andre F.M. Verbeure; Igor Vasilievic Volovich; Wilhelm von Waldenfels; Reinhard F. Werner